The Effect of Mental Health Youth Ambasador Training on Screening Ability and Mental Health Awareness Among Adolescents - Reni Nurhidayah; Lingga Kusumawardhani; Dhita Kurnia Sari (Journal of Health Science Community, 2024)
Adolescent mental health is an increasingly important issue, particularly in Islamic boarding schools (pesantren). SAKTI Remaja is an application developed to enhance mental health services through self-screening features, mental health education, and online counseling. This study aims to evaluate the effectiveness of implementing the SAKTI Remaja application in improving early detection and mental health services in pesantren. This study employs a quasi-experimental design with a pre-test and post-test approach involving students from several pesantren in Kediri. Respondents were given access to the SAKTI Remaja application, and measurements were conducted before and after the intervention. Data were collected using questionnaires assessing knowledge, attitudes, and behaviors related to mental health. Statistical tests were used to analyze differences before and after the intervention. The results indicate a significant increase in students' knowledge and awareness of mental health after using the SAKTI Remaja application (p < 0.05). Additionally, the self-screening feature helped students detect early symptoms of mental disorders, while online counseling services improved access to psychological support. The implementation of this application was also well received by pesantren administrators as part of the School Health Unit (UKS) system. In conclusion, SAKTI Remaja is effective in enhancing mental health awareness and early detection in pesantren. This application has the potential to be an innovative technology-based mental health service, particularly in faith-based educational settings.